Changes in the PM2.5-related environmental health burden caused by population migration and policy implications. (10th March 2021) - Lin, Anqi; Zeng, Zhuotong; Xu, Zhengyong; Li, Xiaodong; Chen, Xuwu; Xu, Wanjun; Liang, Jie; Chen, Gaojie; Li, Xin; Shi, Zhu; Li, Shuai; Li, Jinjin; et al.
Abstract: Over the past few decades, increasingly serious air pollution has occurred in China, which has led to an increasing number of premature deaths caused by fine particulate matter (PM2.5 ). Population migration and rapid urbanization may cause a series of changes in premature deaths. In China, there is a scientific consensus on the severity of the environmental health burden caused by PM2.5 pollution in different areas, but changes in the health burden associated with complex migration remain a significant challenge. This study aims to provide a comprehensive assessment of changes in the environmental health burden of different types of migrants and to facilitate policy development to consider more humanely reducing the environmental health burden of migrants. In this study, we zoned premature deaths based on urban and rural areas extracted by nighttime light data combined with land use data, and analyzed the changes in the environmental health burden associated with intra-provincial urbanization migration and inter-provincial migration. Our research showed that changes in premature deaths caused by intra-provincial urbanization migration and inter-provincial migration accounted for 48.40%–93.38% and 2.61%–34.52% of the total changes in premature deaths, respectively. The highest premature deaths reached 10.16 cases/km 2 in Beijing in 2015. By analyzing the changes in the environmental health burden associated with intra-provincial urbanization migration and inter-provincial migration, we found that few people needed to bear a higher environmental health burden after moving to Hainan, Tibet, Ningxia, Xinjiang, and Guangdong. In contrast, more than 50% of the people moving into Beijing, Liaoning, Shanghai, and Jiangsu had to bear a higher environmental health burden. Fujian and Zhejiang had a healthier environment than the other developed coastal provinces, and had a relatively low environmental health burden. Thus, we introduced corresponding policy suggestions for different migration types. Graphical abstract: Image 1 Highlights: We assess the changes in PM2.5 -related health burden caused by population migration. The intra-provincial urbanization migration and inter-provincial migration in the central region are at a high level. The average health burden on the national population as a result of inter-provincial migration is increasing. Fujian and Zhejiang have a healthier environment than the other developed coastal provinces. Appropriate policy guidance can allow migrants to pursue the economy while bearing less of a health burden.